Parâmetros de monitoramento na produção industrial de componentes em zircônia parcialmente estabilizada com óxido de magnésio - Falvo, Tatiani (Universidade Federal de São Carlos, 2012)
Zirconia has been widely applied on production of structural components, mainly due to its great mechanical properties. However, these properties are associated to the zirconia tetragonal and cubic phases, which are stable only on high temperatures on pure material, being necessary doping the material with some oxides to keep these phases at ambient temperature, on a metastable condition. The industrial production of pieces on zirconia is a function of economical and operational aspects, being more common than chemical methods using the mechanical mixture process for adding the stabilizer oxides to the zirconia powder. On this context, the present work was done in association with an industry of marketing and manufacturing of technical ceramics components, among which stands out the products made on magnesia-partially stabilized zirconia (Mg-PSZ). The aim of this work was the identification of the main aspects associated to the industrial process for the production of zirconia Mg-PSZ that determine the final characteristics of the components, beginning with the characterization of the products of each production stage and the conformation of test bodies for the confirmation of the material stabilization after the sintering process. Thus, it was investigated the production of two batches of powder made from mixing the raw materials by a wet process followed by spray-drying, altering the pH of one slurry, by the addition of an aqueous solution of hydrocholoric acid. It was observed, on the end of the characterization process, that the slurry with reduced pH presented a differential behavior during the spray-drying process, which were responsible for the better mechanical properties on the sintered bodies made from this batch of powder. The analysis of the characterization results allowed the definition of the processing parameters that require a special control to the warranty of final products made on Mg-PSZ, according to the literature review done.
Monitoring parameters for the industrial production of pieces made of magnesia-partially-stabilized zirconia
Keywords: Engenharia de materiais; Óxido de zircônio; Processamento; Óxido de magnésio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA